Designing a Smart Traffic Light Algorithm (HMS) Based on Modified Round Robin Algorithm - Hamarashid, Hozan Khalid; Saeed, Miran Hama Rahim; Saeed, Soran (Kurdistan Journal of Applied Research, 2017)
Nowadays, traffic light system is very important to avoid car crashes and arrange traffic load. In the Sulaimani City / Iraq, there are many traffic problems such as traffic congestion or traffic jam and the amount of time provided manually to the traffic light system. This is the main difficulty that we try to solve. The traffic lights exist but still do not manage traffic congestion due to the fixed time provided for each lane regardless of their different load. Therefore, we are proposing to change the traditional traffic system to smart traffic system (adaptive system). This paper Focuses on the existing system (fixed system), then propose the adaptive one. The main crucial side effects of the existing system are:Emergency cases: congested traffics might block the way of emergencies for instance ambulance, which transports people to the hospitalWasting time of people generally and speciallyDelays, which lead people to not to be punctual, this means people arrive late to the work Wasting more fuels as staying more in the traffics, which affects the environment by increasing pollution.